Kepadatan Daphnia magna yang diberi pakan Effective Microorganisme-4 dosis berbeda - Simanjuntak, Erika E. L.; Lantu, Sartje; Sinjal, Hengky J.; Pangkey, Henneke; Manoppo, Henky; Ginting, Elvie L. (e-Journal BUDIDAYA PERAIRAN, 2022)
This study aimed to examine the effect of probiotic Effective Microorganism-4 (EM4) on the growth rate of the natural feed population of Daphnia magna and to determine the right dose to obtain the highest growth. This research was conducted at the Aquaculture Technology Laboratory, Faculty of Fisheries and Marine Sciences, Sam Ratulangi University, Manado. The time of the study was carried out from April to May 2021. The experimental design used was designed according to a 4 x 4 factorial experimental design in Completely Randomized (CRD). The first factor was the dose of EM4 with 3 levels, namely 0.75 mL, 1 mL and 1.25 mL with 1 control, then the second factor is the time difference (weeks) I, II, III, and IV. The results of the study using the Analysis of Variance (ANOVA) using the JMP application showed 1. The dose difference in the density of daphnia on the culture medium was not significantly affected by the difference between the culture medium and chicken manure (value 'Prob>F)' = 0.1411), 2. The difference in density of daphnia on culture medium was very significant by differences in culture time (Value 'Prob>F' = 0.0003), 3. Interaction, The effect of culture medium factors (EM-4) dose and chicken manure on the density of daphnia changed significantly at the time of the change in the level of the time factor (weeks) (Value 'Prob>F' = 0.0439). Further contrast tests showed that the density of daphnia at week-I was significantly different from the density of daphnia at week-II, week-III, and week-IV and the density of daphnia at week-II, week-III and week-IV were not significantly different.